STRATEGI PENGEMBANGAN AGROINDUSTRI KACANG GOYANG (Studi kasus UD Berusaha di Kelurahan Motoboi Kecil Kecamatan Kotamobagu Selatan) - I Putu Anantawijaya; Agnes E. Loho; Caroline B.D. Pakasi; Lorraine W.Th. Sondakh (Universitas Sam Ratulangi, 2014)
AbstractI Putu Anantawijaya. Strategy Development of ''kacang goyang'' agroindustry, Case Study of ''UD Berusaha'' in the Motoboi Kecil Village, South Kotamobagu Sub District under guidance of of A. E Loho as a Chairman, C. B. D. Pakasi dan L.W. Th. Sondakh as members.Agriculture sector have important roles in Indonesian economy. Agro industry is a strategic to increasing the value added of the agriculture yield through the technology, to expand the job field and also to increase the society income. The objective of this research is to know the development strategy of ''kacang goyang'' agroindustry in ''Motoboi Kecil'' Village, South Kotamobagu Sub District, Kotamobagu City.The collecting data conducted in 3 months from November, 2013 until February, 2014 in ''Motoboi Kecil'' Village, South Kotamobagu SubDistrict, Kotamabagu City. The source of data used were a primary data and secondary data. This analyzes used descriptive analysis and SWOT analysis.The results showed that Gross Profit Margin (GPM) of this company is 13,6%, Net Profit Margin (NPM) is 12,5% , Return On Investment is 1,1% and the profitability is Rp.4.876.115. The results of SWOT analysis showed that development direction of this industry can be handle the quality production through the raising of the level of employment technical skills, the raising of the level of production facility quality, optimizing production, the increasing of innovative product packaging, and increasing the promotion.